2014
DOI: 10.1080/09297049.2014.922170
|View full text |Cite
|
Sign up to set email alerts
|

Working memory deficits in developmental dyscalculia: The importance of serial order

Abstract: Although a number of studies suggests a link between working memory (WM) storage capacity of short-term memory and calculation abilities, the nature of verbal WM deficits in children with developmental dyscalculia (DD) remains poorly understood. We explored verbal WM capacity in DD by focusing on the distinction between memory for item information (the items to be retained) and memory for order information (the order of the items within a list). We hypothesized that WM for order could be specifically related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
70
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 73 publications
6
70
0
Order By: Relevance
“…Our results are also in line with studies in children with DD that have highlighted impaired verbal WM (Raghubar et al, 2010). At the same time, our results go beyond these studies by showing that this deficit seems particularly reliable in conditions where serial order information has to be processed (see also Attout & Majerus, 2015, for similar results in children with DD), and that this deficit is as persistent as mathematical impairment. We should also note that the deficit for order WM was observed independently of the type of verbal material (digits, letters) used, demonstrating the serial order WM impairment observed in the behavioral experiment was not caused by the use of numerical information in that task.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are also in line with studies in children with DD that have highlighted impaired verbal WM (Raghubar et al, 2010). At the same time, our results go beyond these studies by showing that this deficit seems particularly reliable in conditions where serial order information has to be processed (see also Attout & Majerus, 2015, for similar results in children with DD), and that this deficit is as persistent as mathematical impairment. We should also note that the deficit for order WM was observed independently of the type of verbal material (digits, letters) used, demonstrating the serial order WM impairment observed in the behavioral experiment was not caused by the use of numerical information in that task.…”
Section: Discussionsupporting
confidence: 92%
“…It is critical to note here that, despite the fact that the neural substrates that are altered in DD and those that are most directly associated with WM for serial order information appear to be highly overlapping, only one recent behavioral study has explored serial order WM more specifically in DD, showing a deficit for serial order WM in children with DD (Attout & Majerus, 2015). In the present study, we hypothesized that an order WM deficit could be observed also specifically in adults with a history of DD.…”
mentioning
confidence: 96%
“…Currently, only one study has compared working memory tasks that tax the order information or not. Attout and Majerus (2014) reported that children with dyscalculia were impaired in a working memory task only when the processing of order information was required (but not for item information).…”
Section: Discussionmentioning
confidence: 98%
“…Lyons, Price, Vaessen, Blomert, and Ansari (2014) found that whereas number comparison performance (i.e., participants' ability to quickly decide which of two numerals represents a larger quantity) was a better predictor of early symbolic number skills than numerical order processing, from around Grade 6, numerical order processing was the best predictor of children's arithmetic performance (as compared to seven other numerical predictors of arithmetic skills). There is also newly emerging evidence for an order processing deficit in both adults (Rubinsten & Sury, 2011) and children with developmental dyscalculia (Attout & Majerus, 2015). Finally Attout, Noël, and Majerus (2014) demonstrated that memory for order information was a robust predictor of the development of symbolic number skills in young children.…”
mentioning
confidence: 99%